Internal Marketing and its Impact on Organizational Loyalty Case study of the Electricity and Gas Distribution Company - Mascara Branch- - Mohamed Abed Abdel kader; BENAMAR bendouma (Journal of North African Economies, 2025)
This study aims to demonstrate the impact of internal marketing with its dimensions (Training, Motivation, Managerial Support, Empowerment, and Internal Communication), as an independent variable, on organizational loyalty, as a dependent variable, among the employees of the Electricity and Gas Distribution Company -Mascara Branch. We designed a questionnaire for this purpose and diffused 30 copies among administrative employees in the studied company. We used the SPSS program for the analysis and the hypotheses testing. The study’s main results indicate a positive effect of internal marketing with its different dimensions on the organizational loyalty of the studied company’s employees, besides a correlation between the two variables.